Novel Mutations in SH2D1A Gene in X-linked Lymphoproliferative Syndrome, Diagnosed After B-Cell Non-Hodgkin Lymphoma. Issue 4 (May 2017) - Sharapova, Svetlana O.; Fedorova, Alina S.; Pashchenko, Olga E.; Vahliarskaya, Svetlana S.; Guryanova, Irina E.; Migas, Alexandr A.; Kondratenko, Irina V.; Aleinikova, Olga V.
Abstract : Background: X-linked lymphoproliferative disease type I (XLP I) is caused by mutations in the SH2D1A gene and characterized mainly by hypogammaglobulinemia and abnormal response to Epstein-Barr virus with a high predisposition to B-cell non-Hodgkin lymphoma development. Observations: In this article, we describe the experience of 2 centers in Belarus and in Russia that follow 3 male patients who were diagnosed with XLP I after lymphoma development and treatment. Three novel mutations c.51G>C (p.E17D), c.192G>T (p.W64C), and c.53insA (p.K18KfsX67) were found in 3 males patients with XLP I. Two of them did not have any signs of immunodeficiency before B-cell non-Hodgkin lymphoma development. Conclusions: We propose SH2D1A mutational screening be considered in male patients with or without hypogammaglobulinemia who received rituximab treatment for lymphoma and did not recover immunoglobulin G in a year after B-depleting therapy.